Information needs analysis of Filipino fashion and clothing students - Mamuri, Madonna Camille M. (2011)
The primordial function of a library is to provide information. These provisions can exist either through the library's collection, staff, physical facilities and/or services. To efficiently translate these resources into materials that will successfully satisfy the information needs of an information community, it is vital to know more about the information needs of their specific clientele.